Effets Antihypertensifs Des Extraits Aqueux Et Éthanolique Des Graines Fermentées De Parkia Biglobosa (Mimosaceae) Chez Les Rats - Ouolouho, Coulibaly Seydou; Abou, Ouattara; Karamoko, Ouattara; Adama, Coulibaly (European Scientific Journal, ESJ, 2017)
High blood pressure is a major cardiovascular risk factor in the occurrence of stroke, heart failure, kidney failure, and coronary heart disease. They are regarded as the leading causes of death worldwide. The aim of this study was to provide a scientific and pharmacological basis for the traditional use of Parkia biglobosa in the traditional treatment of arterial hypertension. Here, we first looked for certain mineral elements in the fermented seeds of P. biglobosa "soumara". Subsequently, we evaluated the hypotensive and antihypertensive effects of the aqueous and ethanolic extracts from these fermented seeds of P. biglobosa in normotensive and hypertensive rats. The cardiovascular parameters studied were systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR). The results showed that "soumara" is rich in calcium, potassium and magnesium, but low in sodium. Also, plant extracts at doses between 1000 and 2000 mg / kg bw induced a dose-dependent decrease in cardiovascular parameters in healthy rats. The treatment of rats made hypertensive with adrenaline by the ethanolic extract at a dose of 1500 mg / kg bw induced a dose-dependent decrease in cardiovascular parameters until normalization. The aqueous and ethanolic extracts of “soumara” acted in the same way as Nifédipine®, which is a calcium channel blocker.